Movement, habitat use, and early life history of fishes in novel river-reservoir complexes - Pennock, Casey A. (Kansas State University, 2019)
Reservoirs and associated river-fragments are novel ecosystems now common across the globe. Riverine habitats have been transformed and fragmented by dams creating mixed lotic-lentic habitats used as introduction points for non-native species. This has resulted in altered habitats and fish assemblages consisting of species that do not share an evolutionary history. The Colorado River basin is fragmented by dams that create a complex of river fragments and reservoir habitats used by native fishes, such as razorback sucker (Xyrauchen texanus). Low survival of early life stage (ELS) razorback sucker in the Colorado River Basin, USA is thought to cause a recruitment bottleneck, but conservation efforts are limited by a complete mechanistic understanding of causal factors. I used a combination of lab and field studies to examine potential limiting factors contributing to the lack of recruitment by razorback sucker, assessed distribution patterns of the fish assemblage along the San Juan River inflow to Lake Powell, and evaluated movement potential across the entire upper Colorado River basin including between reservoir and riverine habitats. To explore discrepancies in survival of razorback sucker compared to other co-occurring sucker species, I used museum-cataloged fish specimens collected from the San Juan River, Utah to quantify trophic resource use of co-occurring ELS suckers. I evaluated diet diversity and composition using gut content and stable isotope analysis, expecting high overlap in diets among sucker species. Razorback sucker had the lowest diet richness. Although they were smaller and less developed than the other two species, differences in diet item occurrence across sizes and species reflect differences in resource acquisition among ELS suckers that might be related to recruitment bottlenecks. In the next chapter, I assessed species distributions along a 20 km reach of the San Juan River-Lake Powell inflow with the prediction that fish abundance would increase upstream with increasing energy inputs. I identified strong patterns in total number of species and individuals captured with both increasing towards the river inflow by systematically sampling shoreline habitats with trammel nets. Changes in assemblage structure were driven mainly by increases in relative abundance of benthic omnivores, including razorback sucker, towards more transitionary and riverine habitats, but also by increases in predatory species, such as striped bass (Morone saxatilis). River-reservoir inflow areas might provide high-quality feeding areas for both benthic omnivores and piscivores. Lastly, I assessed movement potential of adult razorback sucker across reservoir and river habitats in the upper Colorado River basin using a multi-agency tagging database. Given unimpeded access to upstream riverine habitats, I expected fish to move long distances and readily exchange between riverine and lacustrine habitats. Of 722 fish captured in the Colorado River inflow, 261 were re-encountered and 107 of those were subsequently encountered upstream in the Colorado and Green river systems, or in the San Juan River inflow, with 11 individuals moving at least 586 km. The proportion of fish moving between lacustrine and riverine habitats was estimated in the San Juan River inflow. Within a year of being captured in the reservoir, 29% and 20% of fish in 2017 and 2018, respectively, were detected 30 km upstream in the San Juan River. In 2016-2017, we translocated a total of 303 fish upstream of a 6 m tall waterfall into the San Juan River. Generally, fish did not reside long in the river as 80% were re-encountered downstream of the waterfall within a year. These data show long-distance movements are not limited to a few individuals and illustrate how large river fish can maintain population connectivity in highly altered ecosystems. Managing for the maintenance of diverse movement syndromes (e.g., river-resident versus transient fish) will likely increase population resilience to environmental change. Collectively, this work contributes to an increased knowledge of the ecology and life history of a highly imperiled species and sheds light on fish assemblage use of novel riverine and reservoir habitats that are widespread across the globe.
Keywords: Feeding ecology; River-reservoir inflow; Razorback sucker; Colorado River basin; Fish assemblage